2004
DOI: 10.1017/s0950268804002146
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antigenically and genetically similar influenza C viruses isolated in Japan during the 1999–2000 season

Abstract: Between October 1999 and May 2000, a total of 28 strains of influenza C virus were isolated in four Japanese prefectures: Yamagata, Miyagi, Saitama and Hiroshima. Antigenic analysis showed that the 28 isolates were divided into three distinct antigenic groups, and viruses belonging to different antigenic groups were co-circulating in each of the four prefectures. Phylogenetic analysis of the seven protein genes demonstrated that the viruses having a similar genome composition spread in various areas of Japan d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…We previously revealed that genetically similar strains belonging to the Yamagata/26/81-related lineage were dominantly isolated in four Japanese prefectures (Miyagi, Yamagata, Saitama, and Hiroshima) during the 1999-2000 season (14). The results of antigenic and phylogenetic analyses in the present study also showed that antigenically and genetically similar strains belonging to the Kanagawa/1/76-related lineage were dominantly isolated in various areas of Japan in 2004, along with viruses belonging to other ones in each of the Yamagata, Fukuoka, and Miyagi prefectures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously revealed that genetically similar strains belonging to the Yamagata/26/81-related lineage were dominantly isolated in four Japanese prefectures (Miyagi, Yamagata, Saitama, and Hiroshima) during the 1999-2000 season (14). The results of antigenic and phylogenetic analyses in the present study also showed that antigenically and genetically similar strains belonging to the Kanagawa/1/76-related lineage were dominantly isolated in various areas of Japan in 2004, along with viruses belonging to other ones in each of the Yamagata, Fukuoka, and Miyagi prefectures.…”
Section: Discussionmentioning
confidence: 99%
“…For the first and nested PCR of the NS gene, we used the primers that had been used for NS gene sequencing as reported previously (1,8,14). The primer sequences are well conserved (Ͼ95% identities) among more than 100 influenza C viruses that are registered in GenBank, and we found that influenza A (H3) viruses that circulated in 2004 were not amplified by this PCR procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, AM cells have been shown to be susceptible to influenza C viruses [25,48]. These findings indicate that 9-O-acetyl sialic acid may be carried on Olinked glycoproteins or glycolipids, such as gangliosides [8,49], in AM cells of chicken embryonated eggs.…”
Section: Methodsmentioning
confidence: 99%
“…We suspect that influenza C viruses, which have similar genome composition, are circulating worldwide, as are influenza A and B viruses, because most of the isolates in various areas of the world in the 1970s and 1980s were closely related to the contemporary Japanese viruses in all gene segments, as reported previously (13). Furthermore, future surveillance will try to determine if adult infections are the major means by which influenza C virus spreads.…”
mentioning
confidence: 75%